(untitled) (Ascendens Asia Singapore – Bestlink College of the Philippines Journal of Multidisciplinary Research, 2024)
In this study, the researchers are trying to investigate the benefits of good quality service in customer engagement in selected fast food chains in Quezon City. This is how the company creates a relationship with its customers. This study was conducted in order to investigate the degree of satisfaction level of customers after experiencing fast food service located in Quezon City. Fast food Chain is one of the most successful businesses in the Industry. A fast- food restaurant, also known as a quick-service restaurant (QSR) in the industry, is a specific type of restaurant that serves fast-food meals. It operates and provides standardized ingredients and/or partially prepared foods. Fast food is one of the fastest growing industries in the world, so today’s generation of people is aiming to have a food business with a new and unique taste to the people; people are likely fans of eating foods that are new to them. But on behalf of that there are some issues spreading about services and safety of food some fast food is dealing many complaints from their customers because of bad service, not approachable, the way the employee talk to their customers, and not granting the request of the guest. This kind of service will affect the company. On the other hand, some fast food companies provide good quality service to their customers because they know that it will benefit them. They provide the best service they can. In order to provide good quality service, the industry should make efforts to make service quality a benchmark for every customer to gain a competitive advantage in the restaurant market. Some of the customers encountered good service, and some of them didn’t. Based on the analysis, it was discovered that most of the respondents said that the fast food chain lacks quality service when it comes to providing standard products to the customers. They must change and improve their service for the satisfaction of the customers who eat in their store. Therefore, the overall results of the survey, the store should focus on providing quality products and prioritize the needs of the customers. Accuracy and consistency of the employees towards their customers are the best practices to have successful quality service. Based on the conclusions presented, this study came up with the discussion to recommend the best way to improve the negative feedback of the customers; this fast food lacks providing good quality products on time; therefore, the customers didn’t reach the satisfaction that they expect to happen. Especially based on the findings of the analysis, the store is more focused on having Gen Z and Millennial customers. Nowadays, this generation is eager to get what they deserve when money and food are involved. Also, the store should put more effort into approaching the customers so they feel they are valued. Feedback is helpful. It is the best way to know the wants and dislikes of the customers to avoid complaints.